Analysis of Satisfaction of National Health Insurance Participants on Service Quality in Hospitalized Patients at Kuala Kurun Regional Hospital: A Cross-Sectional Study - Adi Suci Guntoro; K. Hindro Kusumo; Mukhlis Almawan; Yudi Prasety; Merry Krisima; Widya Novalita; Yunita Herliani (Lambung Mangkurat University, 2025)
Health development is one of the national priorities, with the government implementing SJSN to ensure equitable and quality health services. Kuala Kurun Hospital is committed to improving the quality of services in accordance with JKN regulatory standards, maintaining a good level of patient satisfaction, and supporting the achievement of 100% JKN optimization in Gunung Mas Regency. This study aims to describe the level of satisfaction of JKN participants undergoing treatment in the inpatient room of Kuala Kurun Hospital. This study is a descriptive survey study through a quantitative approach, conducted in October - December 2024 with 100 respondents. Patient satisfaction level based on tangible dimension, very satisfied with total score 52 out of 346. Empathy dimension, satisfied with total score 44 out of 318. Reliability dimension, satisfied with total score 50 out of 331. Responsiveness dimension, satisfied with total score 47 out of 317. Assurance dimension, very satisfied with total score 52 out of 346. Inpatient JKN participants generally have satisfaction level at 42.9% for very satisfied, 42.5% satisfied, less satisfied by 13.8% and 0.8% for dissatisfied. JKN patient satisfaction shows that there is a relationship between tangible, empathy, reliability, responsiveness, and assurance with patient satisfaction